Analgesic Effect of Perioperative Escitalopram in High Pain Catastrophizing Patients after Total Knee Arthroplasty. (April 2015) - Lunn, Troels H.; Frokjaer, Vibe G.; Hansen, Torben B.; Kristensen, Per W.; Lind, Thomas; Kehlet, Henrik
<x xml:space="preserve">Abstract</x> Background: Sufficient pain treatment remains a challenge after total knee arthroplasty (TKA), especially in high pain catastrophizing patients. Serotonergic signaling may be involved in pain processing, but the effect of selective serotonin reuptake inhibitors on well-defined postoperative pain has not previously been investigated. The authors hypothesized that perioperative escitalopram would reduce pain after TKA in high pain catastrophizing patients. Methods: A total of 120 pain catastrophizing patients (selected using the pain catastrophizing scale as preoperative screening tool) scheduled for TKA were randomized in a double-blind manner to either 10 mg escitalopram or placebo daily from preanesthesia to postoperative day 6 in addition to a standardized analgesic regime. The primary outcome was pain upon ambulation 24 h after surgery. Secondary outcomes were overall pain during well-defined mobilizations and at rest from 2 to 48 h and from days 2 to 6, morphine equivalents, anxiety, depression, and side effects. Results: Pain upon ambulation (mean [95% CI]) 24 h after surgery in the escitalopram versus placebo group was 58 (53 to 64) versus 64 (58 to 69), the mean difference being −5 (−13 to 3), P = 0.20. Overall pain upon ambulation and at rest from days 2 to 6 was lower in the escitalopram versus placebo group, as was depression score at day 6 (all P ⩽ 0.01 in analyses uncorrected for multiple tests). Side effects were nonsignificant except for reduced tendency to sweat and prolonged sleep in the escitalopram group. No other between-group differences were observed. Conclusions: Escitalopram did not reduce pain upon ambulation 24 h after TKA in high pain catastrophizing patients. Future studies on optimal timing, dose, and duration of selective serotonin reuptake inhibitor treatment might be warranted.